Modelo de autenticação e autorização baseado em certificados de atributos para controle de acesso de aplicações em ambiente distribuído utilizando redes de petri coloridas - Villar, Melissa Vieira Fernandes (2007)
Due to increasing threats inherent to the information systems, the use of authentication and authorization mechanisms based in login and password does not enough to assure the information security. This work proposes a new model of authentication and authorization for distributed applications, based in hash and attributes certificates. Hash is used in the application authentication process, while certificates of attributes specify privileges and other authorization information. Its use is managed by the privilege management infrastructure (PMI). In this work, we describe the architecture and the functioning of the model, as well the processes of the attributes certificates generation, authentication and authorization of the application. The proposed model was specified in Coloured Petri Nets and validated by simulation.